2014
DOI: 10.1021/ja5020103
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Dimensionality of On-Surface Coordination Polymers via Endo- or Exoligation

Abstract: ABSTRACT:The formation of on-surface coordination polymers is controlled by the interplay of chemical reactivity and structure of the building blocks, as well as by the orientating role of the substrate registry. Beyond the pre-determined patterns of structural assembly, the chemical reactivity of the reactants involved may provide alternative pathways in their aggregation. Organic molecules, which are transformed in a surface reaction, may be subsequently trapped via coordination of homo-or heterometal adatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 89 publications
3
55
0
Order By: Relevance
“…The emergence of these new aggregates is also reflected in the XP spectra shown in Figures e, f: N 1s is now split into two chemically shifted species, one at the original BE with a relative peak area of 34 % and a new majority component at a lower BE of 398.1 eV with a relative peak area of 66 %. The lower N 1s BE is characteristic of singly deprotonated amino groups in metal‐coordination bonds . Distinct changes were similarly observed in C 1s, in which the previously observed prominent high BE shoulder appears less pronounced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of these new aggregates is also reflected in the XP spectra shown in Figures e, f: N 1s is now split into two chemically shifted species, one at the original BE with a relative peak area of 34 % and a new majority component at a lower BE of 398.1 eV with a relative peak area of 66 %. The lower N 1s BE is characteristic of singly deprotonated amino groups in metal‐coordination bonds . Distinct changes were similarly observed in C 1s, in which the previously observed prominent high BE shoulder appears less pronounced.…”
Section: Resultsmentioning
confidence: 99%
“…The only example of a related compound is the on‐surface synthesis of pyrene‐fused pyrazaacenes by means of the Schiff‐base reaction . To shed more light on the metal coordination of this important molecular building block on solid surfaces, we present a detailed study of competitive HATP metal coordination on Cu(111) between intrinsic Cu adatoms of the surface and co‐deposited extrinsic Ni adatoms. This choice is motivated by a strong interest in comparing coordination centers with different binding strength and ground‐state electron configurations.…”
Section: Introductionmentioning
confidence: 97%
“…At elevated temperatures DPDI has been shown very recently to eliminate three molecules of H 2 to give 3deh-DPDI (Fig. 1), which interacts with Cu adatoms to form a highly ordered nanoporous network [43]. Difficulties in detecting the coordinated copper adatoms by STM had led us to suggest in an earlier study that the transformation of DPDI stopped at the monodehydrogenated diimine species deh-DPDI which was thought to aggregate via resonance-assisted H bonding between the molecules to form the network [44].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a combination of STM and near edge x-ray absorption fine structure data as well as a re-investigation and re-interpretation of the N1s x-ray photoemission spectroscopy (XPS) signatures, backed up by DFT modeling, we put forward a structural model in which the 3deh-DPDI acts as a bridging exoligand within a surface coordination network [43]. To obtain detailed information about the lateral configuration of the surface-confined 2D MOF, a combination of scanning tunneling microscopy (STM), XPS, and x-ray standing wave (XSW) measurements have been carried out, and the system has been analyzed by extensive DFT modeling.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A variety of functional chemical groups and reaction schemes is found in the literature, such as halogenated precursors, 7−9 boronic acids, 10−12 termethyl-porphyrins, 13 pyridine tautomerization, 14 alkyne coupling, 15,16 amide formation, 17 and reactions involving metal adatoms. 18 −21 Among technologically relevant molecules for organic electronic devices, phthalocyanines (Pcs), metal phthalocyanines (MPcs), and their derivatives have attracted the interest of researchers because of their chemical and optoelectronic properties and their wide applications in the area of gas-sensing devices, light-emitting diodes, solar and fuel cells, organic field effect transistors, pigments, and dyes. 22 The concept of onsurface phthalocyanine macrocyclization between the tetracarbonitrile molecule and Fe on Ag(111) and Au(111) at room temperature was discussed in a previous paper; 23 furthermore, we have recently shown that the reaction between TCNB and Mn has to be activated at 415 K, 24 and the room-temperature study leads to metal−organic networks.…”
Section: ■ Introductionmentioning
confidence: 99%